2013
DOI: 10.1371/journal.pone.0076989
|View full text |Cite
|
Sign up to set email alerts
|

Biological, Functional and Genetic Characterization of Bone Marrow-Derived Mesenchymal Stromal Cells from Pediatric Patients Affected by Acute Lymphoblastic Leukemia

Abstract: Alterations in hematopoietic microenvironment of acute lymphoblastic leukemia patients have been claimed to occur, but little is known about the components of marrow stroma in these patients. In this study, we characterized mesenchymal stromal cells (MSCs) isolated from bone marrow (BM) of 45 pediatric patients with acute lymphoblastic leukemia (ALL-MSCs) at diagnosis (day+0) and during chemotherapy treatment (days: +15; +33; +78), the time points being chosen according to the schedule of BM aspirates required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
7
24
0
2
Order By: Relevance
“…In this study, we focused on the functional alterations of a major and The ability of T-ALL PαS MSCs to support hematopoietic cell growth in vitro was significantly reduced as assessed by CAFC and LTC-IC assays ( Figure 4A-C), which is consistent with a previous report 34 . However, this finding could be attributed to a defect at either HSC or HPC level.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we focused on the functional alterations of a major and The ability of T-ALL PαS MSCs to support hematopoietic cell growth in vitro was significantly reduced as assessed by CAFC and LTC-IC assays ( Figure 4A-C), which is consistent with a previous report 34 . However, this finding could be attributed to a defect at either HSC or HPC level.…”
Section: Discussionsupporting
confidence: 89%
“…Conforti et al studied the morphological features of MSCs derived from pediatric patients with ALL and demonstrated that MSCs at diagnosis do not differ from those obtained during treatment. 29 However, Mallampati et al 30 who studied a mouse BCR-ABL+ ALL model observed that tyrosine kinase inhibitors induce MSC-mediated resistance and MSCs may play an essential role in activation of an alternative survival signaling pathway in leukemic cells that protects leukemic cells from chemotherapy. The effects of Ang 1 and Ang 2 on tumor angiogenesis have been studied in acute myeloid leukemia (AML), [31][32][33] chronic lymphocytic leukemia, 34 multiple myeloma, 35 and myelodysplastic syndrome (MDS).…”
Section: Discussionmentioning
confidence: 99%
“…There are now several reports of MSC changes in human hematologic malignancies such as MDS [23,24], acute lymphoblastic leukemia [25], and AML [14,21,[26][27][28]. Some of these reports suggest increased osteogenic potential [14] whereas others have shown increased adipogenic potential [26,29].…”
Section: Introductionmentioning
confidence: 99%